Thermodynamic Behaviour of Complexation Process Between 15-Crown-5 with Li+, Na+ and K+ Cations in Acetonitrile-Water and 1-Propanol-Water Binary Media - ROUNAGHI, G.H.; MASROORNIA, M.; GHAEMI, A.; RAHCHAMANI, H.A. (Asian Journal of Chemistry, 2010)
The complexation reactions between Li+, Na+ and K+ metal cations with the macrocyclic ligand,15-crown-5 (15C5) have been studied in acetonitrile-water and 1-propanol(1-PrOH)-water binary systems at different temperatures using conductometric method. In all cases, 15C5 forms 1:1 complexes with these metal cations. The values of stability constants of complexes which were obtained from conductometric data show that the stability of complexes is affected by the nature and composition of the mixed solvents used in these studies. In all cases, a non-linear behaviour was observed for the variation of log Kf of the complexes versus the composition of the mixed solvents. In most cases, the stability sequence of the complexes was found to be : (15C5-Na)+ > (15C5-Li)+ > (15C5-K)+. The values of thermodynamic parameters (ΔH°c, ΔS°c) for complexation reactions were obtained from temperature dependence of formation constants of complexes using the van't Hoff plots. The results show that in most cases, the complexation reactions are enthalpy stabilized but entropy destabilized and the values of thermodynamic parameters are influenced by the nature and composition of the mixed solvents.